Peningkatan Hasil Belajar Siswa SDN 5 Gondoharum Kudus Melalui Model TGT dan Media DaperR - Mir'atin Nisai; Irfai Fathurohman; Imaniar Purbasari (Peneliti.net, 2020)
This study aims to describe the improvement in student learning outcomes in grade IV SDN 5 Gondoharum through the TGT learning model and DAPER media. The selection of the TGT model and DAPER media was deemed suitable for natural resource material and poerty on the Cita-Citaku theme. Through the TGT model and DAPER media students can dig up information about the material from some of the question presented, can be done in groups and students not only read the material but are contested so that it does not cause boredom and will get an understanding of learning concepts faster. This type of research is a Classroom Action Research with a total of 16 student research subjects which lasted for 2 cycles. Research in the first cycle obtained the learning outcomes of the student’s knowledge domain with a percentage of completeness 68.75% then in the second cycle obtained the learning outcomes of the student’s knowledge domain with a percentage of completeness 87.50%. based on the results of cycle I and cycle II of the TGT model assisted by DAPER media, it can improve the learning outcomes of Grade IV students of SDN 5 Gondoharum Kudus.